A Total systems study on Genesis Construction and Development Corporation - Gonzales, Jonas R.; Lagunay, Novis T.; Papio, Marivic A.; Venida, Venida A. (College of Engineering, 2003)
Genesis, located in Barrio Napindan, Taguig manufactures steel pipes, Polyethylene (PE) tubings and PVC pipes for potable water pipelines, sanitary pipelines, electrical conduits, and telecommunications main duct. From the analysis of the financial performance of the company, it is observed that there is: *Steadily declining sales and profits for the past four years; *Declining return-on-assets for both plastic and steel pipes (competitors are either stable or increasing); *Steadily declining profit margins in both plastic and steel pipes - steadily declining; *Average (as compared to competitors) net profit margins for both plastic and steel pipes; *Average (as compared to competitors) debt to asset ratios for both plastic and steel pipes; *Low liquidity ratios except the acid ratio for steel pipes; Consistent with the financial indicators, Genesis' market standing is also on the decline, as proved by the: *Decrease in market share in steel pipes - 13% in 2000 to 9% in 2001; *Decrease in market share in plastic pipes - less than 2% (standing for 2002) -lowest among its competitors; Genesis' poor financial and market performance is reflective of a business strategy that is ineffective and inadequate to enable the company to effectively utilize its strengths, work on minimizing (or totally eliminating) weaknesses, capitalize on its opportunities and minimizing threats. Thus, there is a need for Genesis to re-evaluate its overall business strategy in order to improve its performance and increase its market share. The threats to the local steel pipe industry are numerous and very grave. If Genesis wants to assure its continued existence, it should be able to capitalize on its strengths and be able to carve out a specific niche in the market. It should be able to effectively streamline its operations in order to cut down on all unnecessary costs. It should be able to capture a bigger portion of the market but also try to lessen its dependency on government projects. As such, it is recommended that the company reformulate its Vision and Mission statements, set objectives that are specific, measurable, attainable, and realistic and time bound, and set performance measures. Furthermore, it is recommended that the company form a marketing and market research group to look for alternative markets for its pipe products, improve sales and marketing packages, facilitate the construction and maintenance of a website for the company, and study the profitability of indenting finished products. Lastly, the company must form a cross-functional team that will focus on benchmarking and overall process improvement.